Genome-wide analysis of key gene families in RNA silencing and their responses to biotic and drought stresses in adzuki bean - Yongqiang Li; Enze Ma; Kai Yang; Bo Zhao; Yisong Li; Ping Wan (BMC Genomics, 2023)
Abstract Background In plants, RNA silencing is an important conserved mechanism to regulate gene expression and combat against abiotic and biotic stresses. Dicer-like (DCL) and Argonaute (AGO) proteins and RNA-dependent RNA polymerase (RDR) are the core elements involved in gene silencing and their gene families have been explored in many plants. However, these genes and their responses to stresses have not yet been well characterized in adzuki bean. Results A total of 11 AGO, 7 DCL and 6 RDR proteins were identified, and phylogenetic analyses of these proteins showed that they clustered into six, four and four clades respectively. The expression patterns of these genes in susceptible or resistant adzuki bean cultivars challenged with drought, bean common mosaic virus and Podosphaera xanthii infections were further validated by quantitative RT-PCR. The different responses of these proteins under abiotic and biotic stresses indicated their specialized regulatory mechanisms. Conclusions In this study, 24 genes of the DCL, AGO and RDR gene families in adzuki bean were identified, and the sequence characterization, structure of the encoded proteins, evolutionary relationship with orthologues in other legumes and gene expression patterns under drought and biotic stresses were primarily explored, which enriched our understanding of these genes in adzuki bean. Our findings provide a foundation for the comparative genomic analyses of RNA silencing elements in legume plants and further new insights into the functional complexity of RNA silencing in the response to various stresses in adzuki bean.